1988
DOI: 10.1073/pnas.85.13.4610
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional diffusion of Escherichia coli DNA-dependent RNA polymerase: a mechanism to facilitate promoter location.

Abstract: The mechanism of promoter location by DNA-dependent RNA polymerase of Escherichia coli was investigated. The occupancies of DNA fragments carrying the Al promoter of bacteriophage 17 were analyzed as a function of the length of flanking sequences adjacent to the promoter. Competition between the promoters on different fragments showed qualitatively that DNA sequences downstream of the promoter enhanced promoter occupancy, whereas upstream flanking sequences had little or no influence on occupancy. This was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 23 publications
3
66
0
Order By: Relevance
“…On average, roughly half the population of RNAP molecules is mobile over the 2-to 3-m length of the cell on a timescale of 5 to 10 s, with an effective diffusion constant D RNAP of approximately 0.2 m 2 -s Ϫ1 . Remarkably, the D RNAP is comparable to diffusion constants measured in vitro for RNAP sliding along the contour of bare, double-stranded DNA (dsDNA) while nonspecifically bound (10,26,30). The other half of the population is immobile on a timescale of at least 30 to 60 s. We attribute the immobile fraction to RNAP copies that are specifically bound to DNA; at least some of these copies are presumably actively transcribing DNA.…”
mentioning
confidence: 63%
“…On average, roughly half the population of RNAP molecules is mobile over the 2-to 3-m length of the cell on a timescale of 5 to 10 s, with an effective diffusion constant D RNAP of approximately 0.2 m 2 -s Ϫ1 . Remarkably, the D RNAP is comparable to diffusion constants measured in vitro for RNAP sliding along the contour of bare, double-stranded DNA (dsDNA) while nonspecifically bound (10,26,30). The other half of the population is immobile on a timescale of at least 30 to 60 s. We attribute the immobile fraction to RNAP copies that are specifically bound to DNA; at least some of these copies are presumably actively transcribing DNA.…”
mentioning
confidence: 63%
“…Thus, adding the long extension does not detectably increase promoter binding; the data imply that no more than 8% of the long-lived promoter binding events on the long DNA could arise from sliding that originated in the long downstream segment (SI Materials and Methods). A previous study suggested that truncation of segments upstream or downstream had differing effects on promoter occupancy by σ 70 RNAP (20). In our earlier work (7), we truncated the DNA upstream of the glnAp2 promoter (instead of downstream) and measured the effects of the truncation on the kinetics of σ 54 RNAP binding and release using the same methods as in Fig.…”
Section: Rate Of Promoter-specific Binding Is Independent Of the Lengmentioning
confidence: 99%
“…Therefore, σ 54 RNAP reaches its target sequence by a mechanism that differs from the mechanism used by the transcription factors and DNA binding proteins that have been observed to reach their targets by sliding (41)(42)(43). Many previous studies on E. coli RNAP have been interpreted as supporting an FD model for promoter search with sliding distances of hundreds to thousands of base pairs (13)(14)(15)(16)(17)(18)(19)(20)(21). Those studies used a different holoenzyme (σ 70 instead of σ 54 ), and many were conducted at unphysiologically low ionic strength; therefore, it is possible that promoter search by FD occurs under the conditions of those experiments but not our experiments.…”
mentioning
confidence: 99%
“…RNA polymerase binds to DNA and diffuses one-dimensionally to the promoter region (1)(2)(3)(4); it then must make a number of interactions within the promoter as a prerequisite to forming a relatively stable complex. This complex is then in a state that favors isomerization, leading to strand separation from approximately Ϫ12 to ϩ3 with respect to the site of transcription initiation (5).…”
mentioning
confidence: 99%